FRI0723-HPR Physical activity awareness and preferences in rheumatic diseases: a qualitative study. (12th June 2018) - Vitalis, P.; Kouvelas, D.; Kousouri, N.; Lahart, I.; Koutedakis, Y.; Kitas, G.; Metsios, G.
Abstract : Background: Physical inactivity is the fourth leading cause of death (1) and a risk factor for cardiovascular disease (CVD). Patients with rheumatic diseases (RDs), especially rheumatoid arthritis (RA), report low cardiorespiratory fitness levels (2), placing them at an increased risk of premature mortality and CVD. Objectives: The aims of the present study were: a) to evaluate if patients with RDs [RA, ankylosing spondylitis (AS), systemic lupus erythematosus (SLE), osteoarthritis (OA), psoriatic arthritis (PSA), systemic sclerosis (SSC), fibromyalgia (FM), enteropathic arthritis-Crohn's disease (CD), Sjögren's syndrome (SD), Raynaud's disease (RD)] were aware of the physical activity (PA) benefits, and b) to examine their preferences in terms of PA mode and principles (i.e. intensity, duration, frequency). Methods: We designed a questionnaire consisted of dichotomous, open-ended and multiple-choice questions. Patients registered with the Hellenic League Against Rheumatism (EL.E.AN.A), participated by filling in the questionnaire a) online, or b) through phone calls. Content analysis approach was performed for data analysis. Results: Out of the 625 RDs patients registered with the EL.E.AN.A, 197 (31.5 % response rate) returned the questionnaire [137 online and 60 via phone calls (69.6% and 30.4% of the sample, respectively)]. 93 patients had RA (47.3% of the sample, age=54.9±14.5) and 104 (52.7% of the sample, age=50.2±13.9) were diagnosed with other RDs [AS (n=29, 14.7%), SLE (n=25, 12.6%), OA (n=15, 7.6%), PSA (n=10, 5%), SSC (n=8, 4%), FM (n=7, 3.5%), CD (n=4, 2%), SD (n=4, 2%) and RD (n=2, 1%)]. In all patients, subjective beliefs about the benefits of PA, concerned three main themes: a) functional ability, b) mental health and c) overall health. Swimming, was revealed as the most frequent PA mode (n=63, 38.1%). Regarding the principals of PA, patients reported that they preferred moderate intensity (n=76, 41.7%), a duration of "about an hour'' (n=81, 49.3%), a frequency of "2–3 times per week" (n=71, 45.2%) and a blended intervention consisted of group-based, individualised and supervised programmes (n=56, 29.4%). The questionnaire was judged by the patients to be very or fairly understandable in almost all cases (n=196, 99.5%). Conclusions: According to subjective beliefs from the self-reported data of this study, PA is considered from patients to improve physical and mental health in RDs. Additionally, individualisation and supervision of PA programmes were considered amongst the most important parameters of a program for participation. In planning successful PA regimes in RDs, more qualitative studies with representative sample sizes and demographic data are required to address patients' PA needs and preferences and help them adhere to a more physically active lifestyle. References: 1. Lee I, Shiroma E, Lobelo F, Puska P, Blair S, Katzmarzyk P. Effect of physical inactivity on major non-communicable diseases worldwide: an analysis of burden of disease and life expectancy. The Lancet2012;380(9838):219–229. 2. Metsios G, Koutedakis Y, Veldhuijzen van Zanten J, Stavropoulos-Kalinoglou A, Vitalis P, Duda J, et al. Cardiorespiratory fitness levels and their association with cardiovascular profile in patients with rheumatoid arthritis: a cross-sectional study. Rheumatology2015;54(12):2215–2220. Disclosure of Interest: None declared